Ambiguous Loss In The Context OfForced Separation And Forced Adoption - Rozmyrska, Yuliia; Hlova, Iryna (Psychological Prospects Journal, 2023)
Purpose. The article provides a theoretical overview of the theory of ambiguous loss in the focus of physical absence with the psychological presence of a loved one.Methods. To achieve the purpose of the study, the methods of scientific theoretical study were used: analysis, synthesis, structuring, and generalization.Results. Based on the analysis of research on the forced separation of children from their families and its psychological consequences, we can state that the theory of ambiguous loss is important in the situation of forced adoption of illegally displaced children. The theory of ambiguous loss clearly explains the mechanism of experiencing separation from a loved one, when this separation is not fully understood - there is no clear knowledge of the person's status: alive or dead, or the person is physically present but mentally absent, as in the case of dementia. The theory of ambiguous loss clearly explains three types of consequences: immobilization (affects the ability to communicate), consequences at the level of relationships (conflicts due to different views of the situation) and on the personality (manifestations of such conditions as depression, anxiety, guilt, etc.).Conclusions. The model of finding resilience in the face of uncertain loss includes such interrelated structural blocks as finding meaning, tempering mastery, reconstructing identity, normalizing ambivalence, revising attachment and discovering hope. The experience of working with displaced children in El Salvador is also important, because of studying the «disappearance» and "reunification" stages. They formed the basis for adapting the model of resilience in ambiguous loss to study the psychological consequences of forced adoption. The prospects for further research are in the empirical study of the psychological consequences of the forced adoption traumatic situation for children and their families.